Pengaruh Kontrol Diri, Adversity Quotient, Dan Cyberloafing Terhadap Kinerja Karyawan PT Pos Indonesia (Persero) Cabang Bandar Lampung - Daffa Aqiilah, M.; Mardiana, Nova (Shofanah Media Berkah, 2024)
The purpose of this research is to determine the influence of self-control,adversity quotient, andcyberloafing on the performance of employees of PT Pos Indonesia Bandar Lampung branch. The approach used is descriptive quantitative. Data collection techniques use questionnaires and literature study. The sample in the research was 115 respondents with a sampling technique, namelyconvenient sampling. This research uses 3 independent variables, namely self-control,adversity quotient, andcyberloafing and 1 dependent variable, namely employee performance. Hypothesis testing uses the partial test (t) and data analysis uses simple linear regression analysis (partial). This research supports the proposed hypothesis with the self-control variable having a positive and significant effect on employee performance.Adversity quotient positive and significant effect on employee performance.Cyberloafing positive and significant effect on employee performance. Suggestions from this research are that management is advised to provide understanding to employees to do lots of fun things at work even though they are high risk, provide support to employees who make mistakes so that they can easily get up and work as usual, provide understanding when they don't get the appropriate vacation allowance, provide concerns whose opinions differ from those of superiors. Employees are also advised to reduce the intensity of downloading music/films/videos during working hours, so that behaviorcyberloafing can be prevented and routinely record performance achievements after completing a job.